The Influence of Audit Fees on Audit Quality - Annisa Rizki Yanti; Elis Mediawati (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
This study investigates how audit fees impact audit quality. The purpose of this study is to determine the relationship between the effect of audit fees on audit quality in companies listed on the Indonesia Stock Exchange which are categorized as LQ45. This study was conducted using the verification method. Researchers involved 225 LQ45 companies listed on the Indonesia Stock Exchange from 2016 to 2020. The data used comes from secondary data collected through the documentation method. In analyzing the data, this study uses panel data regression statistical testing with a random effect model. The findings of this study are that audit fees are positive to audit quality based on the calculation of panel data regression analysis conducted through the Eviews 9 program.